Design and Develop the Single Jet Nozzles and Fabrication of Single Head Single Jet Spinning Unit - Loganathan R, Nagarajan L, Rajendran S, Kumaran M (Mathematical Statistician and Engineering Applications, 2023)
An attempt has been made through this research work by developing single air jet nozzle and fabricating a single head jet spinning unit for producing air jet yarns with minimum fiber loss and improved yarn characteristics. In the part 1, explain about research work done on newly designed and developed of single jet nozzle and Single head single jet spinning was fabricated. Designed single jet nozzle was carried out in three phases. In the first phase, 11 Nozzles were developed with different dimensions. In the second phase five nozzles were developed with Inner flanged type wrapper fibre chambers in various air fed angle such as 45o, 50 o, 55 o, 60 o and 65 o. In third phase five nozzles were developed with Rectangular shape type wrapper fibre chambers in various air fed angle such as 45o, 50 o, 55 o, 60 o and 65 o. The single jet nozzle consists of Air inlet chamber, Wrapper fibre chamber, false twist chamber and Fasciated yarn chamber. Single head single jet spinning was fabricated and necessary modifications were carried out to achieve high draft range of 10-250 and delivery speed of 150 m/min by servo motor for the drafting zone, winding zone and above nozzle fixed in drafting system.